The Simulation and Analysis of Erosion Corrosion of CO2 Pipelines - A Review - Yuli Panca, Asmara; Muhammad Izzat Nor, Ma'arof (INTI International University, 2022)
Oil and gas production activities use pipeline to distribute raw materials of oil from reservoir to the other processing facilities. These raw materials of oil/crude oils composes elements such as CO2 gas and solid particles which are potential to damage pipe wall through erosion corrosion reactions. Unpredicted design gives fatal impact to the operational process and interrupt continuity of oil distributions. Therefore, it needs corrosion prediction to manage integrity strategies in oil companies. Considering multiple effects created by various corrosive factors, fundamental knowledge to understand corrosion mechanism is important to study in designing corrosion prediction software. To date, numerous corrosion predictions models with different approaches have been developed by oil and gas companies. This paper reviews the applications of fundamental theories of corrosion used by software (ECE, Norsok, Freecorp) in calculating erosion corrosion rate of carbon steel pipes. The concept of existing corrosion software is discussed. Parameters used and range of conditions are also studied. From the results of studies, it can be notified that corrosion predictions software have a prospective tool for determining degradation rate of carbon steel pipes in future. They also have benefits in selecting materials for pipelines and predicting service life of the pipes accurately.